Population genetic differentiation of Daphnia sinensis in a lasting high-phosphorus Chinese lake, Lake Chaohu - Zhang, Kun; Wu, Jianxun; Deng, Daogui; Zhao, Hui; Liu, Qi; Peng, Shuixiu; Zhang, Yanan; Zhou, Zhongze (Frontiers in Ecology and Evolution, 2023)
Ecological shifts (eutrophication) can affect the genetic differentiation of zooplankton populations in lakes. However, the role of environmental change in a long-term high-phosphorus drive genetic differentiation of zooplankton population structure over time, is poorly understood. In this paper, the changes of the genetic diversity and differentiation of Daphnia sinensis population were studied by using the mitochondrial COI gene and microsatellite markers on modern groups (from January to June 2016) and historic groups (obtained from resting eggs in the sediments) in Lake Chaohu. Based on the microsatellite markers, six modern groups were clustered into two clusters (the WG cluster and SG cluster) during the seasonal dynamics, whereas the genetic differentiation of the five historic groups showed a wave-like pattern and had evolved into four clusters. Moreover, the haplotype network showed that six modern groups had one origin center whereas five historic groups had two origin centers based on the mitochondrial COI gene marker. Fu’s Fs neutral test and Tajima’s test indicated that the five historic groups deviated from neutral evolution and reflected a bottleneck effect in the history process. Water temperature and total dissolved phosphorus were obviously associated with the seasonal genetic differentiation of D. sinensis, whereas nitrogen content of the sediments was significantly related to the long-term change of D. sinensis in the high-phosphorus environment. Therefore, the changing pattern of D. sinensis population genetic structure was one of the environmental selections probably combined with co-evolutionary, where rapid-increasing nitrogen level had a large impact on D. sinensis population genetic structure in lasting high phosphorus environment in Lake Chaohu.